Livelihoods after Land Reform in South Africa. (12th December 2012) - Aliber, Michael; Cousins, Ben
<x xml:space="preserve">Abstract</x> Over the past few decades, Zimbabwe, Namibia and South Africa have pursued redistributive land reform as a means to address rural poverty. The Livelihoods after Land Reform (LaLR) study was carried out between 2007 and 2009, to understand the livelihood and poverty reduction outcomes of land reform in each of the three countries. The South African component focused on Limpopo province, and investigated land reform processes, trajectories of change and outcomes in thirteen detailed case studies. This paper summarizes some of the main findings from the South African study, and briefly compares them with findings from Namibia and Zimbabwe. The paper argues that a fundamental problem affecting land reform in both South Africa and Namibia is the uncritical application of the Large‐Scale Commercial Farming (LSCF) model, which has led to unworkable project design and/or projects that are irrelevant to the circumstances of the rural poor. Nevertheless, some 'beneficiaries' have experienced modest improvements in their livelihoods, often through abandoning or amending official project plans.